Meta Analysis of Efficacy and Safety of Prostate Biopsy: A Comparison Between Transperineal and Transrectal Approach - Syah Mirsya Warli; Stivano Rizky Valentino Torry; Dhirajaya Dharma Kadar; Ginanda Putra Siregar; Fauriski Febrian Prapiska (Urology Research and Practice)
Improved prostate biopsy procedures have been developed to overcome traditional limitations, aiming to enhance cancer diagnosis accuracy. To assess the existing knowledge of the effectiveness and risks linked to transperineal (TP) vs. transrectal (TR) prostate biopsy. Approaches: a comprehensive search was carried out in PubMed, Embase, Web of Science, and Cochrane Library to locate all pertinent papers published till June 8, 2023. Data on cancer detection rate and complications after prostate biopsy were gathered and analyzed via Review Manager software. A subgroup analysis was conducted to evaluate the influence of the study type. A total of 19 publications, involving 80133 patients with suspicion of prostate cancer who underwent prostate biopsy, were enrolled in the analysis. The pooled estimate demonstrated no significant differences in the cancer detection rate between TR and TP (risk difference (RD)=0.03; 95% CI: −0.01 to 0.08; P = .12). In terms of complications, the TP approach significantly decreased the risk of rectal bleeding (odds ratio (OR)=0.24; 95% CI: 0.12-0.51; P < .001), fever and urinary tract infection (OR=0.28; 95% CI: 0.15-0.52; P < .001), and sepsis (OR=0.50; 95% CI: 0.28-0.90; P=.02) compared to the TR approach. In conclusion, there was no significant disparity in the cancer detection rate between TP and TR approaches. However, the TP strategy exhibited an advantage over TR due to a reduced risk of infection and rectal bleeding. Further research is needed to validate these results and develop a more efficient diagnostic approach for prostate cancer.